Overcoming disadvantages - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Jane Chepchirchir, Gender Research and Networking Officer for the Kenya National Federation of Agricultural Producers, talks about the many challenges facing women farmers, and how her organisation is addressing them.